Angelica keiskei - characterization and biological activity - Orășan A Sergiu; Răzvan Florin Moruzi; Eugenia Dumitrescu; Florin Muselin; Alexandru O. Doma; Corina Vlad; Erieg A. Mohamed,; Romeo Teodor Cristina (Medicamentul Veterinar, 2021)
This paper supports alternative medicine as well as phytotherapy, which in recent decades has seen an increase in prestige due to the fact that, on the one hand, the increasingly acute resistance to certain antibiotics or antifungal molecules and, on the other hand, the growth of the current traditionalist consumer medicine in both human and veterinary medicine. So, this paper aims to present a plant less known in Romania, but very popular in Japan, South Korea, China and the biological activity of Ashitaba (Angelica keiskei), already established in the countries mentioned above and with possible applications, as an auxiliary or supportive treatment in veterinary medicine.